Institutional shelter to protect adolescent victims of domestic violence: theory or practice? - Diene Monique Carlos; Maria das Graças Carvalho Ferriani; Marta Angelica Iossi Silva; Eliana Mendes de Souza Teixeira Roque; Telma Sanchez Vendruscolo
OBJECTIVE: To understand and analyze, from the perspective of adolescent victims of domestic violence who were cared for in an institution in Campinas-SP, the protective factors to which they are submitted and / or have access. METHOD: This was qualitative research, with data collection occurring through focus groups with 17 adolescents, and semistructured interviews with seven of them; the data analysis was based on content analysis, using a thematic modality. RESULTS: Two themes emerged, entitled Four Walls and Trust. We discuss the context of institutional care, that despite the efforts made contemporaneously, still maintains an authoritarian environment; the importance of the bond and trust established with some employees, acting as protective factors for the adolescents and the protective aspect of religiosity. CONCLUSIONS: It is understood that these considerations should be valued and reinforced through the healthcare services provided to children and adolescents, as they contribute to the promotion of the physical and mental health of this population.